Comparison effect of hyperglycaemia induced mixed meal tolerance and oral glucose tolerance test on body oxidative stress - Önalan Ramazan; Yıldırım Tekin; Caniklioğlu Ayşen (Türk Biyokimya Dergisi)
The mixed meal tolerance test (MMTT) and oral glucose tolerance test (OGTT) are used in the diagnosis of prediabetes and hypoglycaemia. Data suggest that oxidative stress caused by hyperglycaemia during OGTT may have adverse metabolic effects in prediabetic patients. In this study, we aimed to evaluate oxidant and antioxidant levels in OGTT and MMTT.